2010
DOI: 10.1242/jeb.040402
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory modulation of flight in Drosophila is sensitive, selective and rapid

Abstract: There was an error published in J. Exp. Biol. 213,[3625][3626][3627][3628][3629][3630][3631][3632][3633][3634][3635] In the original published version of Fig. 4C, the color code of the y-axes was inadvertently switched. The left y-axis should be red and the right y-axis should be gray. A corrected version of the figure is shown here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 45 publications
2
44
1
Order By: Relevance
“…In Drosophila , behavioral responses to odor can occur with latencies as short as ~80 msec (Bhandawat et al, 2010; Gaudry et al, 2013). Therefore, we began by counting spikes over an 80 msec window (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila , behavioral responses to odor can occur with latencies as short as ~80 msec (Bhandawat et al, 2010; Gaudry et al, 2013). Therefore, we began by counting spikes over an 80 msec window (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies in Drosophila and mammals have also found that single glomeruli can often drive behavior (Bellmann et al, 2010; Bhandawat et al, 2010; Gaudry et al, 2013; Hernandez-Nunez et al, 2015; Mathew et al, 2013; Smear et al, 2013). Notably, we observed clear behavioral responses to single-glomerulus stimuli that elicited firing rates substantially below 50 spikes/s in each of the active ORNs.…”
Section: Discussionmentioning
confidence: 96%
“…One strategy is to turn upwind upon encountering an odor, because odors disperse downwind from the source. Previous studies have shown that Drosophila tend to fly or walk upwind in response to odor (Bhandawat et al, 2010; Budick and Dickinson, 2006; Duistermars et al, 2009; Steck et al, 2012; Thoma et al, 2014; van Breugel and Dickinson, 2014). Whereas flying insects must use visual cues to estimate wind direction from their own self-motion, walking insects can use mechanosensory cues to estimate wind direction (Bell and Kramer, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Control flies can modulate their flying pattern according both to the distance and quality of the odorant stimulus: at far, their fast upwind flight keeps a constant heading, but when they get closer to a stimulatory odor, their heading flight decreases more than with clean air18. During this approach, flies modulate the directionality of their flight by changing both wingbeat frequency and amplitude25265253.…”
Section: Discussionmentioning
confidence: 99%
“…Varied sensory cues can influence Drosophila flight: olfactory stimuli provided by food and carbon dioxide strongly attract flies during flight1819 as do visual cues related to motion and to polarized light2021. During flight, the effect of visual cues can be modulated by mechanosensory stimuli2223 and also by olfactory cues which are bilaterally perceived by flies242526. Recently, chemosensory organs on the wing anterior margin, were shown to be involved in gustatory perception27.…”
mentioning
confidence: 99%